SISTEM INFORMASI PRODUK UNGGULAN DAERAH (SIPUD) KABUPATEN OGAN KOMERING ILIR (OKI) - Putra, Ade (JURNAL ILMIAH MATRIK, 2013)
Systems Information Featured Products Regional (SIPUD) Kabupaten Ogan Komering Ilir (OKI) is a system that manages, organizes data about in formation products produced by OKI both sectors, Agriculture, Plantations, Fisheries, Livestock, Industry, Trade, Mining and Tourism. The system provides in formation of data that can be accessed by the public, which requires a government and investors from a broad, which for the previous Bappeda OKI not have an integrated system that can manage and in form agricultural products from OKI. SIPUD is made using a Content Management System(CMS) Joomla version 1.5. This version has a CMS where ease of module variants and has a more complete and easy to use. The end result of this SIPUD expected to provide in formation that is accurate and always provide updated information on agricultural products by OKI. Keywords: SIPUD, OKI, and CMS